(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This study explores how hormonal imbalance during adolescence affects reproductive health. It analyzes the maturation of the hypothalamic-pituitary-gonadal axis and shows how disruptions during this critical period can lead to long-term issues such as menstrual irregularities, polycystic ovary syndrome, and reduced fertility. The findings highlight the importance of early detection and intervention to prevent chronic reproductive disorders and promote lifelong reproductive well-being.